2022
DOI: 10.1029/2020gl092360
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Skill of Teleconnection Patterns in Twentieth Century Seasonal Hindcasts and Their Relationship to Extreme Winter Temperatures in Europe

Abstract: European winter weather is dominated by several low‐frequency teleconnection patterns, the main ones being the North Atlantic Oscillation, East Atlantic, East Atlantic/Western Russia, and Scandinavian patterns. We analyze the century‐long ERA‐20C reanalysis and ASF‐20C seasonal hindcast data sets and find that these patterns are subject to decadal variability and fluctuations in predictive skill. Using indices for determining periods of extreme cold or warm temperatures, we establish that the teleconnection pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…Hence, it is important to understand how large-scale circulation systems influence peaks of demand and energy production to identify periods of over-and under-supply. Over time, the impact of large-scale atmospheric patterns on extreme winter temperatures mostly does not change, despite slow fluctuations of these patterns [20]. Meteorological conditions preceding energy shortfall are described as anomalous high pressure systems combined with below normal temperatures [11,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is important to understand how large-scale circulation systems influence peaks of demand and energy production to identify periods of over-and under-supply. Over time, the impact of large-scale atmospheric patterns on extreme winter temperatures mostly does not change, despite slow fluctuations of these patterns [20]. Meteorological conditions preceding energy shortfall are described as anomalous high pressure systems combined with below normal temperatures [11,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is important to understand how large-scale circulation systems influence peaks of demand and energy production to identify periods of over-and under-supply. Over time, the impact of large-scale atmospheric patterns on extreme winter temperatures mostly does not change, despite slow fluctuations of these patterns [Schuhen et al, 2022]. Meteorological conditions preceding energy shortfall are described as anomalous high pressure systems combined with below normal temperatures [van der Wiel et al, 2019b, Bloomfield et al, 2018, van der Wiel et al, 2019a.…”
Section: Introductionmentioning
confidence: 99%
“…For most mountainous areas of the Mediterranean region, the occurrence of different winter regimes was closely related to the state of the NAO, although the relationship was weaker in the easternmost part of the Mediterranean Basin [26]. Using indices to determine periods of extremely cold or warm temperatures, it was found that teleconnection patterns, such as the NAO, EA, SCAND and EA/WR, in some regions of Europe correlate or anticorrelate to a large extent with cold or heat waves [30].…”
Section: Introductionmentioning
confidence: 99%